Experiment and optimization of the potato-soil separation and conveying device for a harvester using RecurDyn-EDEM coupling simulation - Pan, Yongfei; Yang, Ranbing; Zhang, Huan; Zhang, Jian; Zha, Xiantao; Qiu, Zhuchuan; Wu, Minsheng (International Journal of Agricultural and Biological Engineering, 2025)
To address issues such as suboptimal separation of potatoes from soil during harvest, weak damage prevention and reduction capabilities in the transport process, and high damage rates, a potato-soil-transport device motion model was proposed based on potato farming practices in northern China (Gansu).The mechanical properties of the separation and transport device and the movement mechanism of the potatoes were analyzed, identifying key factors affecting the separation efficiency of potatoes from soil and potato damage: separation transport device inclination angle (ɑ), machine forward speed (Vm), paddle wheel amplitude (A), and paddle wheel frequency (ƒ). A coupled RecurDyn-EDEM simulation model was constructed to determine the impact of key factors on soil separation efficiency and potato damage. Using an optimization method, the optimal parameter combination for evaluating potato-soil separation was determined: separation transport device inclination angle of 18°, machine forward speed of 4.7 km/h, paddle wheel amplitude of 32.8 mm, and paddle wheel frequency of 6.0 Hz. Field tests showed that the potato-soil separation efficiency was good, with potatoes containing minimal soil and other impurities and experiencing minimal damage. The average potato-soil separation efficiency was 96%, and the average potato damage rate was 2%. Compared to the simulation results, the errors were 0.47% and 0.3%, respectively, meeting the quality requirements for potato harvesting operations. Keywords: potato, separation and transport, coupled simulation, experiment DOI: 10.25165/j.ijabe.20251804.9219Citation: Pan Y F, Yang R B, Zhang H, Zhang J, Zha X T, Qiu Z C, et al. Experiment and optimization of the potato-soil separation and conveying device for a harvester using RecurDyn-EDEM coupling simulation. Int J Agric & Biol Eng, 2025; 18(4): 149–156.